THE UNDERHAND DIVORCE AND ITS IMPACTS ON CHILD CUSTODY ACCORDING TO ISLAMIC LAW AND POSITIVE LAW: (A Study in Seginim Subdistrict, South Bengkulu Regency) - Hardego, Saswin; Muslih, Akhmad; Dahwal, Sirman (Universitas Bengkulu, 2024)
This research examines a. How does the underhand divorce and its impact on child custody in Seginim Subdistrict, South Bengkulu Regency? b. What are the factors leading to underhand divorces and its impact on child custody in Seginim Subdistrict, South Bengkulu Regency? c. How do underhand divorces and its impact on child custody in Seginim Subdistrict, South Bengkulu Regency, align with Islamic Law and Positive Law in Indonesia? This study employs an empirical legal research method. It uses a qualitative approach by determining the research location and informants through in-depth interviews, followed by analysis using a juridical-qualitative method. The research findings are: 1. The underhand divorce is driven by economic reasons and the complexity of legal processes considered burdensome and expensive. This includes cases where the husband leaves the household or infidelity occurs, forcing couples to choose underhand means to end the marriage. The impact of such divorces in Seginim includes injustices related to iddah as waiting period and hadanah support for ex-wives and children. Many do not fully receive these rights post-divorce, worsening their financial and social conditions. 2. Factors leading to underhand divorces in Seginim Subdistrict, South Bengkulu Regency, and its impact on child custody, as follows: Traditional Practices: Underhand divorces have been a long-standing custom in Seginim society. Although Islamic law considers such divorces valid, the state does not recognize them. Lack of Legal Awareness: The people of Seginim often do not understand or do not care about national legal regulations regarding divorce. Personal Issues and Economic Constraints: Divorce is often viewed as a stigma, leading to it being carried out quietly. Impact on Child Custody: The unofficial divorce process can negatively affect child custody arrangements. 3. Underhand divorce affects not only the legal status of the spouses but also significantly impacts child custody. Under both Islamic law and Indonesian positive law, divorces that do not go through the court can result in legal uncertainty that negatively affects children's rights, such as financial support and custody rights. Therefore, it is crucial for divorcing couples to undergo the divorce process through the court to ensure legal certainty and protection of children's rights. Keywords: Divorce, Underhand, Child